The mitochondrial uncoupling as a promising pharmacological target against cancer - Roberto Fernández Acosta; Octavio Piñeros; Gilberto L. Pardo Andreu (GarVal Editorial Ltda., 2019)
Context: Mitochondria represent a key intracellular signalling hub that is emerging as important determinants of numerous aspects of cancer development and progression. In this sense, the organelle constitutes a promising target for the development of novel anticancer agents. Despite the negative history, mitochondrial uncoupling has recently proposed as a pharmacological target against cancer, but little is known about the mechanisms involved. Aims: To demonstrate the role of mitochondria in tumor formation and to describe how targeting of mitochondria uncoupling can be beneficial in the therapy of these diseases, which affect a large human population. Methods: The data for this systematic review were collected from three popular databases including PubMed, Google Scholar, and Scopus and included in the search terms the words "mitochondrial uncoupling" and "cancer". The influence of mitochondrial uncoupling on cells physiology that could lead to cancer cells death, invasion and metastasis was critically appraised from relevant researches. The anticancer effects of small molecules mitochondrial uncouplers and their anticancer mechanisms were also discussed. The present dataset finally included 201 published articles. Results: It was found that the mitochondrial uncoupling-mediated responses possibly involved in the anti-cancer/anti-metastatic effects include Ca2+ homeostasis and bioenergetics disruption, mitochondrial membrane potential dissipation, reactive oxygen species generation, mitochondrial dynamics alteration, and gene expression modulation. Conclusions: Overall, this critical review suggests that mitochondrial uncoupling could be an interesting pharmacological target to be considered in the design and synthesis of novel anti-cancer compounds with optimal physic-chemical and biopharmaceutical properties and improved safety profiles.